English Language Teachers' Perceptions of Using Technology in Teaching English Language at Al-Asmarya University - Dr. Mufida Ali Ghwela (Abhat Journal, 2023)
This research investigates the English language teachers' perceptions towards the use of technology in English language teaching. The study followed a mixed method research design, in which a questionnaire was used to gather quantitative data as the main research tool, while a semi-structured interview provided the qualitative data. Data were collected from 26 EFL lecturers at Al-Asmarya Islamic University in Zliten, Libya. The collected quantitative data were analysed using Microsoft Excel software, while the qualitative data were categorized into themes. The analysis of data seems to indicate that the main challenges faced by EFL lecturers at Al-Asmarya Islamic University in Zliten in teaching with regard to the use of technology are the lack of internet connection, computers, technical assistance, and the lack of teachers with sufficient competence and experience to use technology. It was also found that teachers in higher education have a positive perception towards the use of technology in teaching. The finding asserts that the EFL curriculum in Libyan universities needs to consider incorporating technology into teaching instruction in order to achieve the objective of the teaching and learning process.